Government institutional support for fostering SME’s innovation in Western Balkan countries - Petkovska, Mirchevska Tatjana; Daniloska, Natasha; Boshkovska, Diana; Petkovski, Vladimir; Majstoroska, Jasmina (Economic Development, Journal of the Institute of Economics – Skopje, 2019)
The Western Balkans countries, including Republic North Macedonia, recognized the importance of innovation policy and strategy for the development of SME’s. In this paper, a theoretical and comparative analyses of the policies and infrastructure for fostering innovation has been implemented, with accent on the government institutional support for innovative SME’s as sub-dimension for creating and implementing the innovation policy in Western Balkans countries.
Keywords: innovation; SME’s; innovation policy; Western Balkan countries